2012
DOI: 10.1111/j.1552-6569.2011.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions Progression in Migraine with Aura: A Clinical and MRI Longitudinal Study

Abstract: Our study demonstrates that in migraine with aura WMLs number can progress over time and suggests an association between aura features and WMLs progression. Studies with a higher number of patients are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…In CAMERA-1, 10 the authors examined the relationship between attack frequency and WMAs, and suggested that WMAs could arise due to the cumulative impact of repeated episodes of regional cerebral ischemia during a migraine attack. A longitudinal study from Italy, 31 which was not included in our summary tables because it lacked nonmigraine controls, suggested WMA progression in MA at follow-up MRI after about 33 months. The study reported a correlation of the number of new WMAs with attack frequency (p 5 0.03) and aura duration (p , 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In CAMERA-1, 10 the authors examined the relationship between attack frequency and WMAs, and suggested that WMAs could arise due to the cumulative impact of repeated episodes of regional cerebral ischemia during a migraine attack. A longitudinal study from Italy, 31 which was not included in our summary tables because it lacked nonmigraine controls, suggested WMA progression in MA at follow-up MRI after about 33 months. The study reported a correlation of the number of new WMAs with attack frequency (p 5 0.03) and aura duration (p , 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed migraine, especially migraine with aura to be a risk factor for WMLs [21, 22]. Additionally, the risk for ischemic stroke was reported to be higher in patients with migraine with aura than with migraine without aura [23].…”
Section: Discussionmentioning
confidence: 99%
“…69 Hyperintensities in the white matter. 61,65,[70][71][72]77 Increased iron deposition in the periaqueductal grey, putamen, globus pallidus, and red nucleus. 70,[78][79][80]83 Increased stroke risk, especially in the posterior circulation.…”
Section: Modality Findingsmentioning
confidence: 99%
“…An important study recently conducted by Dinia and colleagues 77 used MRI to prospectively evaluate longitudinal changes in the white matter lesions in migraineurs with aura. The subjects were followed for a mean time of 33.2 months and were evaluated for cerebrovascular risk factors.…”
Section: 99mentioning
confidence: 99%